Formation testing : pressure transient and contamination analysis - Chin, Wilson C. (Scrivener Publishing, Wiley, 2014)
"The book provides more than formulations and solutions: it offers a close look at formation tester development 'behind the scenes, ' as the China National Offshore Oil Corporation opens up its research, engineering and manufacturing facilities through a collection of interesting photographs to show how formation testing tools are developed from start to finish"--